A relação entre governança corporativa e o nível de manutenção de caixa das firmas - Kilpp, Anderson (Universidade do Vale do Rio dos Sinos, 2015)
The present dissertation exists because of the big discussion on managers decisions about firm’s cash level. The purpose of this research is to verify if there is a relationship between companies’ level of corporate governance and their degree of liquid assets. For that, we develop a regression model witch includes corporate governance indexes, liquidity level and control variables presented on this area researches. Data comes from brazilian public companies listed in BM&FBovespa and included in IBRA (Índice Brasil Amplo) index, considering the period of 2010 to 2013. We ran statistical regressions with panel data and fixed effects. The results present non significant coefficients for corporate governance indexes IGC1 and IGC2, built by the author. However, BM&FBovespa’s index (NGC) delivers consistent results with negative correlation between corporate governance and level of cash. The interpretation of this results lead to the idea that there are agency problems resulting from the possibility of expropriation of liquid resources and from private interests of managers. Furthermore, we verify evidence of assimetric information problems, once it seems managers try to compensate the high cost of debt with cash.
Keywords: Governança corporativa; Manutenção de caixa; Assimetria de informação; Corporate governance; Cash holding; Assimetric information; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis